Economic Recession in Nigerian Arabic Literature: Exploring some Ilorin Literati - A. Asalejo, Abdulrafiu (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The economic recession is one of sensitive state from which Nigeria is suffering a lot at this current time, it is a state of contraction in economic activity or a form of extraordinary economic stagnation. Many Nigerian Literati and writers in Arabic paid great attention to this matter with prose and poetry to the extent that some of them wrote a book to discuss this issue like Abdul Gani Adebayo Alabi who named his book "Almaja’at", he joined his voice to the voice of poets who condemn this situation, and we find among them who illustrate this economy recession showing how the people are suffering in this state of depression, some of them express the cause for this depression, and some who compare economic life in Nigeria to economic life in other countries like Egypt for example. We also see those who have come up with a proposal that suggest the solution of economic recession. The aim of this research is to present and study some of these literary works in an analytical study that highlights their contents and significance.